2008 IEEE International Conference on Bioinformatics and Biomedicine 2008
DOI: 10.1109/bibm.2008.80
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Protective Linear B-Cell Epitopes Using Evolutionary Information

Abstract: Mapping B-cell epitopes plays an important role in vac-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
(45 reference statements)
3
13
0
Order By: Relevance
“…These findings also corroborate previous studies on the use of feature selection methods to improve prediction performance [15-17]. Interestingly, feature extraction using the Bayes Feature Extraction approach as implemented here is intuitively similar to the application of position-specific scoring matrix (PSSM) profiles for predicting protective linear B-cell epitopes by EL-Manzalawy et al [21]. In that study, it was shown that the Naive Bayes classifier trained using PSSM profiles significantly outperformed the propensity scale-based methods and simple binary encoding with SVM in predicting protective linear B-cell epitopes.…”
Section: Resultssupporting
confidence: 87%
“…These findings also corroborate previous studies on the use of feature selection methods to improve prediction performance [15-17]. Interestingly, feature extraction using the Bayes Feature Extraction approach as implemented here is intuitively similar to the application of position-specific scoring matrix (PSSM) profiles for predicting protective linear B-cell epitopes by EL-Manzalawy et al [21]. In that study, it was shown that the Naive Bayes classifier trained using PSSM profiles significantly outperformed the propensity scale-based methods and simple binary encoding with SVM in predicting protective linear B-cell epitopes.…”
Section: Resultssupporting
confidence: 87%
“…This suggests that discriminating protective antigens from non-antigens may be much easier than discriminating antigens from non-antigens. A similar observation has been reported in [57], where we showed that classifiers trained to predict protective linear B-cell epitopes have better predictive performance than classifiers trained to predict linear Bcell epitopes. We conjecture that protective antigens can be discriminated from antigens on the basis of some sequence features.…”
Section: Resultssupporting
confidence: 67%
“…The existing methods which rely on propensity scale approach are Parker et al [5], Karp lus et al [7], Emin i et al [8], PREDITOP [9], PEOPLE [10], BEPITOPE [11] and BcePred [12]; wh ile the recent existing methods which rely on machine learn ing approach are BepiPred [13], A BCPred [14], Söllner and Mayer [15], Chen et al [16], Söllner et al [17], BCPred [18], FBCPred [19], El-Man zalawy et al [20] and COBEpro [21].…”
Section: Introductionmentioning
confidence: 99%